2022
DOI: 10.1155/2022/3067526
|View full text |Cite
|
Sign up to set email alerts
|

Boswellia serrata Extract, 5-Loxin®, Prevents Joint Pain and Cartilage Degeneration in a Rat Model of Osteoarthritis through Inhibition of Inflammatory Responses and Restoration of Matrix Homeostasis

Abstract: Osteoarthritis (OA) is a chronic, progressive joint disease associated with pain, functional impairment, and diminished quality of life in affected individuals. At a societal level, it also has a high economic burden. Boswellia serrata has been reported to have potent anti-inflammatory, antiarthritic, and analgesic effects. The aim of this study was to explore the therapeutic potential and possible underlying mechanism of 5-Loxin®, a standardized Boswellia serrata extract, in a rat model of OA. The OA model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…lowered anti-collagen antibodies, cartilage oligomeric matrix protein, C-reactive protein, TNF-α, IL-6, nitric oxide, PGE 2 , and COX-2 levels, along with reduction in arthritic index, paw volume, and joint inflammation ( Majeed et al, 2021 ). In our study, we achieved significant LM modulation with BSR starting at 10 up to 100 μg/mL, which are pharmacologically relevant concentrations, as BSR/5-Loxin® were efficacious when supplied at comparable or even higher doses (i.e., 40–200 μg/g) ( Majeed et al, 2021 ; Shin et al, 2022 ), as stated above. In light of the effects of BSR/5-Loxin® on inflammatory mediators and enzymes in these studies on animal diseases, it is interesting that exogenously added SPMs reduced the levels of pro-inflammatory cytokines like TNF-α and IL-6 as well as of MMPs and nitric oxide in comparable arthritis models ( Chiang and Serhan, 2020 ).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…lowered anti-collagen antibodies, cartilage oligomeric matrix protein, C-reactive protein, TNF-α, IL-6, nitric oxide, PGE 2 , and COX-2 levels, along with reduction in arthritic index, paw volume, and joint inflammation ( Majeed et al, 2021 ). In our study, we achieved significant LM modulation with BSR starting at 10 up to 100 μg/mL, which are pharmacologically relevant concentrations, as BSR/5-Loxin® were efficacious when supplied at comparable or even higher doses (i.e., 40–200 μg/g) ( Majeed et al, 2021 ; Shin et al, 2022 ), as stated above. In light of the effects of BSR/5-Loxin® on inflammatory mediators and enzymes in these studies on animal diseases, it is interesting that exogenously added SPMs reduced the levels of pro-inflammatory cytokines like TNF-α and IL-6 as well as of MMPs and nitric oxide in comparable arthritis models ( Chiang and Serhan, 2020 ).…”
Section: Discussionsupporting
confidence: 66%
“…Hence, in a rat OA model, 5-Loxin® (100 and 200 μg/g body weight, p.o.) relieved OA joint pain along with suppression of PGE 2 and LTB 4 levels ( Shin et al, 2022 ). Likewise, in rats with collagen-induced arthritis, BSR (40 and 80 μg/g body weight, p.o.)…”
Section: Discussionmentioning
confidence: 99%
“…Kimmatkar and colleagues, in their 2003 RCT, found that when compared with placebo controls, Boswellia extract was significant in decreasing knee pain and swelling [344]. This was also reflected in later studies, either in novel formulations or in combination with other extracts [345][346][347][348]. Neither of these studies, however, compared the efficacy of the extract with any common NSAID; hence, the results cannot be considered conclusive.…”
Section: Boswellia Serratamentioning
confidence: 99%
“…Numerous randomized controlled studies researched the safety and efficacy of B. serrata extract in the treatment of osteoarthritis (OA) (53)(54)(55)(56)(57)(58)(59)(60).…”
Section: Boswellia In Osteoarticular Inflammatory Diseasesmentioning
confidence: 99%